THE ASPIRING CIO AND CISO a career guide to developing leadership skills, knowledge, experience, and behavior - West, Darryl (Packt Publishing Ltd., 2024)
Strategically build your brand, master soft skills, and craft a powerful plan, propelling yourself into the dynamic world of executive leadership in the digital technology and cybersecurity domain Key Features Discover a targeted 90-day plan to set yourself up for success in both CIO and CISO roles Develop essential interpersonal skills to succeed in executive leadership roles Learn survival skills for thriving and avoiding burnout in strategic roles Purchase of the print or Kindle book includes a free PDF eBook Book Description Explore the intricacies of CIO and CISO roles with The Aspiring CIO and CISO by David Gee. This book leverages Gee's 20+ years of digital and cyber leadership experience, providing real-world insights, making it a valuable resource for those navigating the evolving landscape of the C-suite. Tailored to entry-level, mid-level, and senior managers looking to advance to the C-suite, this book serves a unique purpose in the realm of career guidance. The narrative speaks directly to individuals uncertain about their readiness for CIO or CISO roles, offering a personal mentorship experience that goes beyond technicalities. Armed with insights into crafting a powerful 90-day plan, you'll be well-equipped to catapult into CIO or CISO roles successfully. Beyond technical proficiency, the book instills survival skills, ensuring longevity and helping you prevent burnout in these pivotal positions. Additionally, by mastering the art of brand development and soft skills, you'll grasp the interpersonal dynamics crucial for executive leadership. This book is an indispensable guide for ambitious professionals, offering foresight and empowerment to thrive in the digital age. By the end of this book, you'll emerge with strategic dexterity, confidently steering your career trajectory towards the C-suite. What you will learn Develop a compelling personal brand for CIO and CISO roles Gain mentorship through expert tips, techniques, and proven strategies to navigate executive leadership Be well prepared for interviews, with insights into interview questions as well as questions you can ask Gain insights into managing high-stakes situations and leading your organization through crises Practice leadership through real-life CISO and CIO scenarios Find out how to establish and leverage professional networks crucial for your advancement to CIO or CISO roles Who this book is for This book is for entry-level, mid-level, and senior managers aspiring to ascend to the C-suite as CISOs or CIOs. The book is also aimed at IT and security professionals who want to gain the skills, knowledge, and experience to take on senior executive roles in the digital age.
Keywords: Computer security -- Vocational guidance; Chief information officers -- Training of; Leadership; Sécurité informatique; Orientation professionnelle; Chefs des services de l'information; Formation